Ultrasound‐guided serratus anterior plane block combined with parasternal block in subcutaneous implantable cardioverter defibrillator implantation: Results of a pilot study. Issue 7 (3rd June 2020) - Uran, Carlo; Giojelli, Angela; Borgogna, Donato Antonio; Morello, Gerardo; Marullo, Flavio; Iodice, Pietro; Greco, Angelo; Accogli, Michele; Guido, Alessandro; Palmisano, Pietro
Abstract: Background: The standard approach to subcutaneous defibrillator (S‐ICD) implantation often requires general anesthesia or anesthesiologist‐delivered deep sedation. Ultrasound‐guided serratus anterior plane block (SAPB) combined with parasternal block (PSB) has been proposed in order to provide anesthesia/analgesia and to reduce the need for sedation during S‐ICD implantation. In this pilot study, we compared the double‐block approach (SAPB + PSB) with the single‐block approach (SAPB only) and with the standard approach involving local anesthesia and sedation. Methods: We prospectively enrolled 22 patients undergoing S‐ICD implantation: in 10, the single‐block approach was adopted; in 12, the double‐block approach. As a control group, we retrospectively enrolled 14 consecutive patients who had undergone S‐ICD implantation under standard local anesthesia and sedation in the previous 6 months. Intra‐ and postprocedural data, including patient‐reported pain intensity, were collected and compared in the three study groups. Results: The double‐block approach was associated with a shorter procedure duration than the single‐block and standard approaches (63.3 ± 7.9 vs 70.1 ± 6.8 vs 76.9 ± 7.8 min; P  < .05) and with a lower dose of local an aesthetic for infiltration (18.9 ± 1.7 vs 27.5 ± 4.6 vs 44.6 ± 4.0 cc; P  < .001). Both the double‐ and single‐block approaches were associated with lower pain intensity at the device pocket and the lateral tunneling site ( P  < .05). The double‐block approach proved superior to the other two approaches in controlling intraoperative pain at the parasternal tunneling site ( P  < .05). Conclusions: In our study, SAPB combined with PSB was superior to SAPB alone and to the standard approach in controlling intraoperative pain during S‐ICD implantation. In addition, this approach resulted in shorter procedure durations.